A new annual fish of the genus Simpsonichthys (Cyprinodontiformes: Cynolebiidae) from the upper Rio Jequitinhonha basin, Brazil - Nielsen, Dalton Tavares Bressane; Pessali, Tiago Casarim; Dutra, Guilherme Moreira (Zootaxa, 2017)
A new species of Simpsonichthys is described from the upper rio Jequitinhonha basin, Minas Gerais, eastern Brazil. It is diagnosed from all congeners by presenting an A-patterned frontal squamation. Additionally, males of the new species differs from all congeners by the color pattern of body, the color of iris, the absence of contact organs in the pectoral fin, presence of scales on anal-fin base, pectoral-fin length, caudal fin length, and eye diameter. Females of the new species can be diagnosed from remaining congeners by the pectoral-fin length. The conservation status of the new species is evaluated. Comments on the relationships of the new species within the genus Simpsonichthys are presented.